2020
DOI: 10.1152/jn.00406.2019
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation neural mass and field modeling

Abstract: The Wilson–Cowan population model of neural activity has greatly influenced our understanding of the mechanisms for the generation of brain rhythms and the emergence of structured brain activity. As well as the many insights that have been obtained from its mathematical analysis, it is now widely used in the computational neuroscience community for building large-scale in silico brain networks that can incorporate the increasing amount of knowledge from the Human Connectome Project. Here, we consider a neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 129 publications
(123 reference statements)
1
73
0
Order By: Relevance
“…Jansen and Rit [23] demonstrated that transitions between seizures and healthy brain activity could be viewed as transitions between coexisting oscillatory solutions. A similar approach for this model (without gap junctions) can be found in [9]. With gap junctions switched on in both populations (…”
Section: Excitatory-inhibitory Network: Bifurcation Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Jansen and Rit [23] demonstrated that transitions between seizures and healthy brain activity could be viewed as transitions between coexisting oscillatory solutions. A similar approach for this model (without gap junctions) can be found in [9]. With gap junctions switched on in both populations (…”
Section: Excitatory-inhibitory Network: Bifurcation Analysismentioning
confidence: 95%
“…with theoretical work by Laing on how to treat gap-junctions [30] and by Coombes and Byrne [10] on the inclusion of realistic synaptic currents (governed by reversal potentials and dynamic conductance changes). Recent work in [9] has also considered the inclusion of finite action potential speeds. In this paper we consider a synthesis of modelling work to date on developing a new class of mean-field models fit for use in complementing neuroimaging studies, and present some new results emphasising the important role of local gap-junction coupling in shaping brain rhythms and waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete surface-based models are defined on a (highly-sampled) cortex and are therefore finite-dimensional. In several studies, region-based and discrete surface-based models are collectively referred to as networks of neural masses [17,31,32]. Continuous surface-based models are better known as neural field models and are defined on the entire cortex and are thus infinite-dimensional [23,26,33].…”
Section: Discussionmentioning
confidence: 99%
“…Region-based models are constructed by parcellating the cortex into a number of regionsof-interest (ROIs), placing a local model in each ROI, and connecting them according to a given connectome (see [2,17,32] for reviews). The ROIs are usually obtained from structural or functional cortical atlases and the number of ROIs is in the order of a hundred or less.…”
Section: Discussionmentioning
confidence: 99%